Mode coupling internal resonance characteristics of submerged floating tunnel tether - Sheng-nan Sun (Springer, 2021)
Article Highlights When the tether is only subjected to in-plane or out of plane harmonic loads, if the first-order in-plane and out of plane frequencies of tether are close to each other, the tether is prone to occur modal coupling internal resonance. Since the frequencies of in-plane and out-of-plane of the tether are not exactly the same. Thus, when modal coupling internal resonance occurs, the external excitation frequency is closer to the first-order modal frequency of the non-load acting plane. When excitation amplitude is a fixed value, increasing the damping ratio may inhibit the occurrence of mode coupling internal resonance and effectively reduce the mid-span amplitude of tether.